2005
DOI: 10.1007/s00415-005-0868-y
|View full text |Cite
|
Sign up to set email alerts
|

Impairment–oriented training and adaptive motor cortex reorganisation after stroke: a fTMS study

Abstract: In a sample of 28 subacute anterior circulation ischemic stroke patients with severe arm paresis, reduced motor cortex excitability (increased motor thresholds, reduced MEP amplitudes, reduced number of active points) and a reduced conduction velocity in the corticospinal system were found in the affected hemisphere. At the same time motor cortex topology for the abductor pollicis brevis (APB) representation was comparable for the affected and non-affected hemisphere. Considerable arm motor recovery (Fugl-Meye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 41 publications
(46 reference statements)
5
51
0
5
Order By: Relevance
“…Thus, based on this selection, 21 studies were excluded and 18 studies proceeded for further analysis (Figure). This number was reduced to 16 because Langhammer and Stanghelle 39,40 and Platz et al 41,42 refer to the same data; therefore, these 4 papers have been considered as 2 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, based on this selection, 21 studies were excluded and 18 studies proceeded for further analysis (Figure). This number was reduced to 16 because Langhammer and Stanghelle 39,40 and Platz et al 41,42 refer to the same data; therefore, these 4 papers have been considered as 2 studies.…”
Section: Resultsmentioning
confidence: 99%
“…38,39,41,43,44,45,49,50,[51][52][53] Seven studies used blinding of all subjects. 38,39,43,44,48,51,52 Eleven studies used independent assessors for outcomes 38,39,41,43-46,48 -51 In 11 studies, 85% of the subjects were measured for at least one key outcome, 38,39,[41][42][43][44][45]48,49,53,54 whereas in 10 studies, an intentionto-treat analysis was performed. 38,39,41,[43][44][45][46]48,49,53 The results of between-group statistical comparison were reported in all studies.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Our literature search identified 28 relevant training studies that quantified neural plasticity changes for further analysis to determine if inclusion in this meta-analysis was appropriate (Brouwer & Ambury, 1994;Carey et al, 2002;Cramer, 2004;Cramer et al, 1999;Cramer et al, 1997;Foltys et al, 2003;Jang et al, 2003;Jang et al, 2005;Könönen et al, 2005;Koski et al, 2004;Levy et al, 2001;Liepert, Bauder et al, 2000;Liepert, Graef et al, 2000;Liepert et al, 2001;Lindberg et al, 2004;Luft et al, 2004;Muellbacher et al, 2002;Nelles, 2004;Nelles et al, 2001;Newton et al, 2002;Park et al, 2004;Platz et al, 2005;Schaechter et al, 2002;Seitz et al, 2004;Sonde et al, 2001;Stinear & Byblow, 2004;Wittenberg et al, 2003). For meta-analysis inclusion, each article was originally examined for changes in neural representation measured in four areas of interest: (1) primary motor cortex (M1), (2) supplementary motor area, (3) dorsal premotor area, and (4) cingulate area.…”
Section: Subjects: Study Selection and Inclusion/exclusion Criteriamentioning
confidence: 99%
“…The 13 remaining studies (Carey et al, 2002;Jang et al, 2003;Jang et al, 2005;Könönen et al, 2005;Koski et al, 2004;Liepert, Bauder et al, 2000;Liepert et al, 2001;Luft et al, 2004;Muellbacher et al, 2002;Nelles et al, 2001;Platz et al, 2005;Schaechter et al, 2002;Stinear & Byblow, 2004) used upper extremity training as a rehabilitation treatment while testing stroke subjects in both the sub-acute and chronic stages of recovery. The necessary data from the 13 treatment studies were extracted by two authors and separately confirmed by the other three authors of this meta-analysis.…”
Section: Subjects: Study Selection and Inclusion/exclusion Criteriamentioning
confidence: 99%
“…The proprioceptive and exteroceptive sensory information data are transduced by sensory structures that in turn transfer a subset of their information to the central nervous system which, following yet another transformation, issues a set of motor commands [4] [6] [8]. The mechanical coupling between musculoskeletal elements and the muscles controlling them is yet another transformation of information in the system [14] [15] [16] [17]. The control problem revolves around the specific transfer functions that describe each transformation [6] [14] [15].…”
Section: Introductionmentioning
confidence: 99%